CONTEMPORARY MATHEMATICS EDUCATION AND ITS RELATION TO ECONOMIC THEORY AND PRACTICAL-METHODOLOGICAL ASPECTS OF THE CASE - Klinkov, G.T; Naydenova, V.N (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
The mathematical training of the contemporary stage of the educational paradigm in Bulgaria significantly changed both its applied and especially methodical function. The necessity of examining the issue related to the mathematical text problems determined the boundaries of our research volume. The subject is oriented towards verifying the possible boundaries in which a constructive learning task with a text element can be solved on the basis of unification and algorithmization of a single methodic approach or mechanism. The proximity of text tasks to native language learning greatly facilitates the teacher's work as the child forms semantic and lexical models that then help him to recognize the different text in which the new moment is the description of the quantitative aspects of phenomena.At the beginning of the course in mathematics, which actually proceeds without the existence of verbal specimens, gradually progressing to the objectification of models, which in a small part the student knows from the social system in which he lives and is able to typify them it kind present in the mathematical condition of tesks tasks.